Why prisons are not “The New Asylums” - Ben-Moshe, Liat (Punishment & society, 2017)
This paper will offer an antidote to the axiom that jails and prisons are becoming “the new asylums” in the U.S. Without disregarding the reality of having disproportioned numbers of people with disabilities (psychiatric, cognitive, learning disabilities in particular) in jails and prisons, I will caution against declarations that prisons are becoming “the new asylums” in the U.S. and offer a more nuanced explanation that incorporates perspectives from those critiquing incarceration, institutionalization and psychiatry to shed new light on the connections between incarceration and deinstitutionalization at present and in the past. The claims that post-deinstitutionalization people with psychiatric disabilities were “abandoned to their fate” and re-incarcerated in jails and prisons via being homeless will be critically examined. While doing so, I will also discuss the processes of disablement inherent in prisons and in being housing insecure.